A multi-level structural assessment strategy for reinforced concrete bridge deck slabs. Issue 2 (1st February 2017) - Plos, Mario; Shu, Jiangpeng; Zandi, Kamyab; Lundgren, Karin
Abstract: This paper proposes a multi-level assessment strategy for reinforced concrete bridge deck slabs. The strategy is based on the principle of successively improved evaluation in structural assessment. It provides a structured approach to the use of simplified as well as advanced non-linear analysis methods. Such advanced methods have proven to possess great possibilities of achieving better understanding of the structural response and of revealing higher load-carrying capacity of existing structures. The proposed methods were used for the analysis of previously tested two-way slabs subjected to bending failure and a cantilever slab subjected to a shear type of failure, in both cases loaded with concentrated loads. As expected, the results show that more advanced methods yield an improved understanding of the structural response and are capable of demonstrating higher, yet conservative, predictions of the load-carrying capacity. Nevertheless, the proposed strategy clearly provides the engineering community a framework for using successively improved structural analysis methods for enhanced assessment in a straightforward manner.